Analisis Financial Distress dengan Model Altman Z Score pada Sektor Perkebunan di Bursa Efek Indonesia Periode 2014-2022 - Surono, Yunan; Irwanto, Telly Zuvilla (Universitas Batanghari Jambi, 2024)
This research aims to analyze the comparative analysis of potential bankruptcy (financial distress) models using the first, revised and modified Altman model for plantation sector companies on the Indonesia Stock Exchange. Financial distress can be used to determine and monitor a company's financial condition, so that it is hoped that they will be able to make better decisions to maintain the stability of company performance, including in public, private, manufacturing or service companies of various sizes. This research uses data and facts related to 11 companies from 21 listed companies in the plantation sector on the Indonesia Stock Exchange. The results of the research show that the issuer shares that have the best financial performance based on the financial distress analysis respectively and those that have not experienced bankruptcy are the LSIP and SMAR issuers, while the ones that have experienced the least pressure are the AALI issuers